Recollections of Nick Martin: 1983–1986. (22nd April 2020) - Kendler, Kenneth
Abstract: This short essay recounts the author's interactions with Nick Martin in the years they both worked with Lindon Eaves at Virginia Commonwealth University. Although coming from very different academic traditions, they became close colleagues building their young careers together. Nick generously shared his statistical genetics expertise and the author taught Nick a thing or two about psychiatric illness.